2012
DOI: 10.1002/chin.201205151
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Structure—Activity Relationship of 1‐ and 2‐Substituted 1,2,3‐Triazole Letrozole‐Based Analogues as Aromatase Inhibitors.

Abstract: Synthesis and Structure-Activity Relationship of 1-and 2-Substituted 1,2,3-Triazole Letrozole-Based Analogues as Aromatase Inhibitors. -1,2,3-Triazole analogues, e.g. (III) and (V), of letrozole are synthesized by employing the "click" chemistry as the key step. The presence of a para-cyano group and two aryl groups seems to be important for good activity. Compounds (IIIe) and (Ve) could serve as potential lead compounds. -(DOIRON, J.; SOULTAN, A. H.; RICHARD, R.; TOURE, M. M.; PICOT, N.; RICHARD, R.; CUPERLOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In conclusion, novel imidazo[1,2-a]pyridine based 1,2,3-triazole amide derivatives were designed, synthesized, and confirmed by 1 H NMR, 13 C NMR, 19 F NMR, MS Spectra, and elemental analysis, and evaluated for in vitro anticancer activity against two human cancer cell lines, HeLa and MCF-7. The obtained results clearly revealed that most of the tested compounds such as 9d, 9b, 9c, 9f, and 9j were found to be more effective inhibitors of growth of two cell lines with IC 50 values that are close to that of standard drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, novel imidazo[1,2-a]pyridine based 1,2,3-triazole amide derivatives were designed, synthesized, and confirmed by 1 H NMR, 13 C NMR, 19 F NMR, MS Spectra, and elemental analysis, and evaluated for in vitro anticancer activity against two human cancer cell lines, HeLa and MCF-7. The obtained results clearly revealed that most of the tested compounds such as 9d, 9b, 9c, 9f, and 9j were found to be more effective inhibitors of growth of two cell lines with IC 50 values that are close to that of standard drug.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] ] It has been discovered that triazole moieties showed vast range of biological activities through diverse mechanisms like enzymatic action, receptor-mediated mechanism, etc. The 1,2,3-triazole derivatives are well known for various biological activities such as anti-HIV, [12][13][14][15] anticancer, [16][17][18][19] antibacterial activities. [20,21] On the other hand, imidazopyridine showed a wide range of biological activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was performed using dimethyl sulfoxide as a solvent at atmospheric pressure of acetylene. 9a b The best results were observed for the aryl-substituted azides, benzyl azide, and n -nonyl azide. Sterically hindered azides, such as o -substituted phenyl azides and 1-functionalized benzyl azides, gave triazoles 104 in low to moderate yields (Scheme 52 ).…”
Section: (3+2) Cycloadditionmentioning
confidence: 98%
“…Sterically hindered azides, such as o -substituted phenyl azides and 1-functionalized benzyl azides, gave triazoles 104 in low to moderate yields (Scheme 52 ). 9a b…”
Section: (3+2) Cycloadditionmentioning
confidence: 99%